2019
DOI: 10.1002/anie.201908420
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Activity of the Hydrated Proton Is Substantially Higher than That of the Hydroxide Ion

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.org/10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…47 The implication is that SFG spectroscopy may not provide information about the acidity of the OTL probed by our experiments. 18,19 The absence of H 3 O + proton donors at the OTL of pH > 4 water is consistent with the pH dependence of the electrophoretic mobilities of air bubbles, which display an isoelectric point in the pH 3−4 range. 15,48 Bubbles and droplets are negatively charged above pH ∼ 4 and positively below pH ∼ 4 arguably due to the presence of excess OH − and H 3 O + ions on their surfaces.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…47 The implication is that SFG spectroscopy may not provide information about the acidity of the OTL probed by our experiments. 18,19 The absence of H 3 O + proton donors at the OTL of pH > 4 water is consistent with the pH dependence of the electrophoretic mobilities of air bubbles, which display an isoelectric point in the pH 3−4 range. 15,48 Bubbles and droplets are negatively charged above pH ∼ 4 and positively below pH ∼ 4 arguably due to the presence of excess OH − and H 3 O + ions on their surfaces.…”
Section: Discussionsupporting
confidence: 66%
“…Recent DFT–MD simulations of the structure of an air–water interface containing one hydronium ion concluded that surface-specific sum frequency generation (SFG) spectroscopy is blind to the effects induced by H 3 O + ions in the structure of OTL water [the binding interfacial layer (BIL) in the original report] . The implication is that SFG spectroscopy may not provide information about the acidity of the OTL probed by our experiments. , …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In view of the contradictory conclusions, it is not unlikely that the four above-mentioned causes (and maybe others) are all simultaneously at play. The literature on the various topics is exhaustive and extending year by year [16][17][18], and it would be futile to even try and discuss all the information that is being accumulated.…”
mentioning
confidence: 99%
“…Protons at water/vapor interfaces play a key role in atmospheric chemistry and environmental science. , They have been the topics of extensive theoretical and experimental studies for decades, but good understanding of the surface affinity of protons on the microscopic and quantitative level is still lacking. Molecular dynamics (MD) simulations generally predict that protons (H + ) could appear at the interface in the form of hydronium (H 3 O + ), while the quantitative details, such as the adsorption free energy and the depth profile of ion concentrations, depend very much on the molecular model and interaction potentials assumed. Several experimental approaches have been used to verify the qualitative conclusion from the simulations, but extension of these efforts to quantitative characterizations of the proton adsorption remains challenging . This largely limits our knowledge of the underlying mechanisms and the role of protons in many relevant interfacial processes.…”
mentioning
confidence: 99%